Fintech Innovations and their Role in Developing Islamic Finance Products – Blockchain Technology as a Model - (Journal of Economic Additions, 2026)
This paper aims to highlight the role of adopting financial technology innovations, particularly blockchain, in enhancing the quality of Islamic financing products. It emphasizes the characteristics and applications of this technology within the financial sector, particularly in Islamic finance.The study concludes that Islamic banks must embrace financial technology to keep pace with the digital era and leverage services offered by fintech companies. This transformation presents numerous opportunities, especially with blockchain technology, which facilitates complex financing structures and Sharia-compliant transactions, ultimately aiding in the development of innovative Islamic financial products and services.Jel Classification Codes: G02,G21.
Keywords: Financial Technology; Islamic Banks; Islamic Financing Products; Blockchain Technology.